Apelin Promotes Endothelial Progenitor Cell Angiogenesis in Rheumatoid Arthritis Disease via the miR-525-5p/Angiopoietin-1 Pathway - Chang, Ting-Kuo; Zhong, You-Han; Liu, Shan-Chi; Huang, Chien-Chung; Tsai, Chun-Hao; Lee, Hsiang-Ping; Wang, Shih-Wei; Hsu, Chin-Jung; Tang, Chih-Hsin (Frontiers in Immunology, 2021)
Angiogenesis is a critical process in the formation of new capillaries and a key participant in rheumatoid arthritis (RA) pathogenesis. The adipokine apelin (APLN) plays critical roles in several cellular functions, including angiogenesis. We report that APLN treatment of RA synovial fibroblasts (RASFs) increased angiopoietin-1 (Ang1) expression. Ang1 antibody abolished endothelial progenitor cell (EPC) tube formation and migration in conditioned medium from APLN-treated RASFs. We also found significantly higher levels of APLN and Ang1 expression in synovial fluid from RA patients compared with those with osteoarthritis. APLN facilitated Ang1-dependent EPC angiogenesis by inhibiting miR-525-5p synthesis via phospholipase C gamma (PLCγ) and protein kinase C alpha (PKCα) signaling. Importantly, infection with APLN shRNA mitigated EPC angiogenesis, articular swelling, and cartilage erosion in ankle joints of mice with collagen-induced arthritis. APLN is therefore a novel therapeutic target for RA.